EVALUASI PROSEDUR PENGENDALIAN INTERN ATAS PIUTANG USAHA PADA PT SPS (DEPO GEDANGAN) - Enny Istanti (AKUNTANSI 45, 2020)
in performing company”s activities, absolute officency principle in hold and implemented. A company is demanded to be able to permorm with other companies. One of several factors in reaching offciency and effectiveness is sufficient intern control on every company activities. Internal control is organization planning and all methods, procedure, and policies which is coordinated in a business unit. Problem solving method that being used in this thesis writing is qualitative analysis method. Here, the writer is performing direct research, thah is by data collection technique, through interview and document analysis thaht suitable with writer needs as the basic of intern control system implementation of account receivable and good delivery that being implemented at PT SPS (Depo Gedangan).Based on above research, it can be concluded that intern control system at billing prosedur and good delivery is not sufficient yet, because at good delivery procedure there is no right policy for good delivery to the customer couse it”s influence the billing process. In order to solve company”s problem, there is a need improvement which later will be able to help company”s development that is by make policy wint no unload goods if not print newa item receipt (BPB) and with implement a billing system in each Center Distrik (DC).